Diversidad de insectos scolytinae del bosque Protector Pedro Franco Dávila del Recinto Jauneche, Cantón Palenque, año 2015 - Zambrano Barcos, Ciro Ludovico (2016)
This research was conducted in the Bosque Protector Pedro Franco Dávila (BPPFD), located in the canton Palenque, enclosure Jauneche, coordinates 1o 20.00' South latitude and 79o 35.00' latitude east, with an area of 137 ha. The overall objective was to evaluate the diversity of insects Scolytinae in two areas of BPPFD to determine the diversity of insects Scolytinae 20 flight interception traps were placed during the months of May, June and July 2015 eight genera and 13 species were collected, with a total of 1471 specimens of which 772 and 699 specimens the intervention area and unhampered respectively. Xyleborus gender was the most abundant with 86.53% and 71.82 % specimens in the intervention area and unhampered respectively. The Shannon diversity index was 0.92 and 1.08 for the operated area for unhampered which indicated that for both sampling areas diversity was high, also found that there is no statistically significant difference between the areas sampled area. The Jaccard similarity index indicated that the evaluated areas have a ratio of 83.33 %. The population fluctuations of Scolytinae in the months of May, June and July 2015 were peaks in the second week and third week, is from 15 to 30 May 2015.